Identification and regulation pattern analysis of long noncoding RNAs in meibomian gland carcinoma. (7th December 2018) - Song, Xin; Fan, Jiayan; Jia, Renbing; Zhou, Yixiong; Ge, Shengfang; Zhang, Ge; Wang, Haibo; Fan, Xianqun
Aim: To identify long noncoding RNAs (lncRNAs) and to elucidate regulation patterns of lncRNAs in meibomian gland carcinoma (MGC).Materials & methods: We used RNA-Seq, gene ontology, ClueGO, Ingenuity Pathway Analysis and co-expression network analyses to profile the expression and regulation patterns of lncRNAs and mRNAs in MGC.Results: We identified 500 lncRNAs and 326 mRNAs as differentially expressed. Co-expression regulatory networks with lncRNAs and mRNAs were constructed. The differentially expressed mRNAs and lncRNAs were enriched by fundamental biological functions that are implicated in the inflammatory signaling pathway and tumor proliferation ( IL6 and PTGS2 ).Conclusion: LncRNAs might play important roles via the competing endogenous RNA regulation pattern in MGC tumorigenesis and contribute to the molecular pathogenesis of MGC.